ANALISIS KOMPETENSI PENELITI PADA BALAI PENELITIAN DAN PENGEMBANGAN BUDIDAYA AIR PAYAU - Prianggoro, Bimo Adi (JPSI (Journal of Public Sector Innovations), 2016)
The issue of the competence of civil servants become a central issue in line with the bureaucratic reform program. Required an appropriate system to improve the competence of civil servants. Based on personnel data, civil servants who occupied the post of Researchers at RICA shows the number of dominant. The amount is expected to be offset by a corresponding mastery of competencies required. This study aimed to analyze the level of Researchers competence at RICA. The researchers competence is measured using three variables, namely knowledge, skills, and attitudes with survey method. The research result states that most researchers have been able to master the competencies required. It is recommended that the leader can allocate training for competencies assessed indicator has weaknesses and budgets for human resource development activity.